A Study on the Self-Sustaining Solar Module by Utilizing Solar Cell from Non-Degradable Waste - Farah Aina Mohd Jamal; Juliza Jamaludin; Syarfa Najihah Raisin; Bushra Naeem (Institut Teknologi Nasional, Bandung, 2021)
ABSTRACTPresently, Malaysia is fostering growth in the green energy sector in order to reduce its carbon emissions and contribute in the fight against global warming. Renewable Energy (RE) such as solar cell could no longer be considered as a green technology because at the end of their lifecycle, they become non- biodegradable waste which in turn constitutes pollution and contributes to global warming. Thus, the aim of this research is to study a self-sustaining solar module produced by upcycling solar cells from non- biodegradable waste. Several solar cells from electronic devices were reused in this study. The results obtained show that a combination of 4V, 3V and 2V reused solar cells produced 10.20V and 47.9mW of power. This indicates that the proposed upcycled solar module is feasible and has the potential to aid in the promotion of clean and renewable energy use in order to attain the desired sustainable development goals.Keywords: solar module, self-sustaining, solar cell, non-degradable waste